2020
DOI: 10.3390/ijms21155534
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Potential LncRNA Biomarkers in Hirschsprung Disease

Abstract: Hirschsprung disease (HSCR) is a neurocristopathy defined by intestinal aganglionosis due to alterations during the development of the Enteric Nervous System (ENS). A wide spectrum of molecules involved in different signaling pathways and mechanisms have been described in HSCR onset. Among them, epigenetic mechanisms are gaining increasing relevance. In an effort to better understand the epigenetic basis of HSCR, we have performed an analysis for the identification of long non-coding RNAs (lncRNAs) by qRT-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…In recent years, a growing number of studies have shown that non-coding RNAs (ncRNAs) play a significant role in HSCR onset [ 29 ]. Since the main goal of this study is to further clarify the epigenetic basis of HSCR, we decided to further examine the DMRs associated with ncRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, a growing number of studies have shown that non-coding RNAs (ncRNAs) play a significant role in HSCR onset [ 29 ]. Since the main goal of this study is to further clarify the epigenetic basis of HSCR, we decided to further examine the DMRs associated with ncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it should be noted that these ncRNAs ( MEG3 , AFAP1-AS and MIR195 ) were included in the gene list of promising candidates according to the enrichment analysis. It should be mentioned that two differentially methylated genes encoded for lncRNAs previously described as potential genes with a role during ENS based on their expression in human EPCs ( IPW and NR2F1-AS1 ) [ 29 ]. It has been reported an aberrant expression level of MEG3 , AFAP1-AS and MIR195 in gut tissues from HSCR patients, which suppressed cell migration and proliferation [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two contributions from Borrego’s group focus on Hirschsprung disease, a disorder caused by a defective proliferation, differentiation, survival, and/or migration of enteric precursor cells originating from the neural crest [ 5 , 6 ]. Current tests employed for the diagnosis of Hirschsprung disease are burdensome, and thus the availability of a simple disease biomarker would provide immense benefit to the patient and clinician.…”
mentioning
confidence: 99%
“…Using a combined experimental and computational approach, Villalba-Benito et al report the dysregulation of five candidate genes related to PAX , which are potentially involved in the development of the enteric nervous system and implicated as the cause of disease onset [ 5 ]. In the group’s commentary, Torroglosa et al report the dysregulation of three long non-coding RNAs (lncRNAs) in the enteric precursor cells of patients with Hirschsprung disease, compared to healthy controls [ 6 ]. lncRNAs are transcripts with a length greater than 200 nucleotides and have regulatory roles in gene expression at the epigenetic, transcriptional, translational, post-transcriptional, and post-translational levels in many biological processes.…”
mentioning
confidence: 99%